Encyclopedia of terrorism - Chalk, Peter, 1967- (ABC-CLIO, 2013)
"Provides an up-to-date and comprehensive reference tool for understanding the latest developments in national and international terrorism, one of the most pressing security challenges facing the world today."--Resumé vydavatele
Chronologický přehled
Terminologický slovník
Keywords: terorismus; terrorism; encyklopedie; elektronické knihy; encyclopedias; electronic books